"Just-In-Time" Simulation Training Using 3-D Printed Cardiac Models After Congenital Cardiac Surgery. (March 2016) - Olivieri, Laura J.; Su, Lillian; Hynes, Conor F.; Krieger, Axel; Alfares, Fahad A.; Ramakrishnan, Karthik; Zurakowski, David; Marshall, M. Blair; Kim, Peter C. W.; Jonas, Richard A.; Nath, Dilip S.
Background: High-fidelity simulation using patient-specific three-dimensional (3D) models may be effective in facilitating pediatric cardiac intensive care unit (PCICU) provider training for clinical management of congenital cardiac surgery patients. Methods: The 3D-printed heart models were rendered from preoperative cross-sectional cardiac imaging for 10 patients undergoing congenital cardiac surgery. Immediately following surgical repair, a congenital cardiac surgeon and an intensive care physician conducted a simulation training session regarding postoperative care utilizing the patient-specific 3D model for the PCICU team. After the simulation, Likert-type 0 to 10 scale questionnaire assessed participant perception of impact of the training session. Results: Seventy clinicians participated in training sessions, including 22 physicians, 38 nurses, and 10 ancillary care providers. Average response to whether 3D models were more helpful than standard hand off was 8.4 of 10. Questions regarding enhancement of understanding and clinical ability received average responses of 9.0 or greater, and 90% of participants scored 8 of 10 or higher. Nurses scored significantly higher than other clinicians on self-reported familiarity with the surgery (7.1 vs 5.8; P = .04), clinical management ability (8.6 vs 7.7; P = .02), and ability enhancement (9.5 vs 8.7; P = .02). Compared to physicians, nurses and ancillary providers were more likely to consider 3D models more helpful than standard hand off (8.7 vs 7.7; P = .05). Higher case complexity predicted greater enhancement of understanding of surgery ( P = .04). Conclusion: The 3D heart models can be used to enhance congenital cardiac critical care via simulation training of multidisciplinary intensive care teams. Benefit may be dependent on provider type and case complexity.